UPAYA PENINGKATAN PENGETAHUAN SISWA SEKOLAH DASAR MENGENAI WARISAN BUDAYA SEBAGAI USAHA PELESTARIAN BUDAYA KAMPUNG TUGU - Nasution, Isman Pratama (Bhakti: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to enhance the understanding of elementary school students in Kampung Tugu Portugis regarding the importance of Cultural Heritage and Intangible Cultural Heritage in their environment. Kampung Tugu is a historic area shaped by the cultural fusion of Portuguese Mardijkers and the Betawi community. Based on interviews with local sources, it was found that there is a lack of cultural heritage education among the younger generation, particularly at SDN Semper Barat 01. The program activities included educational sessions, site visits, the creation of pocketbooks, a performance of Tugu keroncong music, and the development of a wall magazine. Evaluation through pre-tests and post-tests showed a significant increase in students’ understanding after the program. This initiative is expected to foster a sense of ownership and pride among students toward their local cultural heritage, as well as to encourage active participation in its preservation. The results of this program also highlight the importance of collaboration between academics, schools, and the community in preserving cultural heritage through engaging and locally based educational approaches.